Evolutionary Relationships Among the Oryza Species - Wambugu P.W.; Nyamongo D.; Ndjiondjop, M.N.; Henry R.J. (Springer, 2018)
Despite being highly studied, the evolutionary relationships in the Oryza genus have remained inconsistent and inconclusive. The origin and domestication history of Asian rice has particularly remained contentious. This chapter discusses the evolutionary relationships between various species in the Oryza genus, with a special focus on the application of current advances in genomics in understanding the various evolutionary dynamics. Advances in genomics are offering opportunities for resolving the origin of cultivated rice and clarifying phylogenetic and evolutionary relationships between the various Oryza species. Analysis of genomes of cultivated rice and their putative progenitors is providing useful information such as unusually diverged genomic regions, which provides vital insights into rice evolution, domestication and demographic history. However, with the increase in whole genome sequence data, it appears that data analysis and subsequent interpretation may now present the next challenge in efforts aimed at resolving this hot debate. The use of nuclear and whole chloroplast genome sequences is helping define the relationships between the recent newly discovered Australian taxa which are believed to be novel gene pools. In this chapter, we have also discussed the challenges faced in efforts aimed at resolving evolutionary relationships in the Oryza genus.